Phenolics profile and anti-proliferative activity of Cyphomandra Betacea fruit in breast and liver cancer cells - Abdul Mutalib, Maisarah; Ali, Faisal; Othman, Fauziah; Ramasamy, Rajesh; Rahmat, Asmah (SpringerOpen, 2016)
Cyphomandra betacea (C. betacea) belongs to the Solanaceae family. This study was aimed to evaluate the anti-proliferative of C.betacea crude extract against selected cancer cell lines (breast and liver cancer) and to identify the polyphenolics profile (phenolic acids and flavonoids) of C. betacea fruits. Anti-proliferative effect of the extracts was examined using MTT (3-(4,5-dimethylthiazol-2yl)-2,5-diphenyltetrazolium bromide) assay, followed by cell morphology analysis using acridine orange and propidium iodide double staining.The phenolics profile was characterized using high-performance liquid chromatography (HPLC). C. betacea extract showed a high cytotoxic effect against liver and breast cancer cell lines with the IC50 value of 30 and 80 µg/ml, respectively. Phenolics profiling showed that C. betacea extract has a wide variety of polyphenolic compounds which are the responsible substances underlying the cytotoxic activity. The microscopic examination analysed by acridine orange and propidium iodide double staining showed that viable cells of the liver and breast cells were well rounded, large and intact green nuclei compared with the treated cells that characterized by apoptotic features (shrunken nuclei with a less quantity of cytoplasm).The present study demonstrated that the anti-proliferative properties of C. betacea fruits were partially attributed to the rich phenolics content. It supports the hypothesis that C. betacea fruits have potential as an effective agent in cancer therapy.